Paired nerve stimulation with selective compensation effect - Leukhin, Alexey; Mikhailova, Yuliya; Masaev, Dinar; Belov, Grigorii; Toschev, Alexander; Fatykhova, Elsa; Vallverdú, Jordi; Talanov, Max (Frontiers in Neuroscience, 2024)
BackgroundIn this study we investigate the selective compensation of paired peripheral nerves in healthy humans, focusing on distinct axonal conduction velocities in different fibre types. Using paired associative stimulation (PAS) with adjustable parameters, we aimed to modulate and compensate for neuronal activity along the median nerve.MethodsSix healthy volunteers (3 male, 3 female, aged: 22–49) participated in the current study. We conducted 30 experiments with the following protocol. A pair of pulses with the following parameters were applied to each volunteer: amplitude, pulse width and inter-pulse delay was generated by the dual-core programmed microcontroller STM32H745xI/G while values were set by one-board computer Jetson Nano. The microcontroller provided a pair of pulses to the DAC that applied it to nerve stimulation sites via a stimulator. During experiments, we used the following ranges: (a) current amplitudes [0–20mA], (b) pulse width [250–500 μs] and (c) delays [50–250 μs]. As the measurement of the stimulation effectiveness, we used the finger's contraction angles.ResultsOur findings reveal a significant selective compensation (inhibitory) effect over the motor responses, demonstrated through variations in finger displacement angles. By optimizing individual parameters-pulse width, inter-pulse delay, and compensatory currents—we successfully induced motor response compensation effects. Notably, consistent compensatory effects were observed across all volunteers using a pulse width of (250 μs) and an inter-pulse delay of (50 μs).DiscussionThese results highlight PAS's potential for developing non-invasive neuromodulation devices. However, further research is required to evaluate its efficacy in individuals with spasticity and upper motor neuron deficits.